Gender Diversity and Disorders of Sex Development: Time for Greater Medical Awareness in Bangladesh: Distinguishing Gender Identity from Biological Variations in Sex Development (Journal of Paediatric Surgeons of Bangladesh, 2026)
Abstract not availableJournal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 1-3